Sandpile experiments and statistical analysis for slope failure, failure shape, and frequency distribution - W.S.G. Fernando; Yota Togashi; Teppei Kato; Masahiko Osada (Soils and Foundations, 2025)
Natural slopes, which occur without human intervention, are susceptible to failure triggered by events such as earthquakes and heavy rainfall. The characteristics of these failures, including the shape of the slip surface and the magnitude of collapse, vary significantly due to factors like the direction of seismic motion, ground heterogeneity, and unsteady rainfall infiltration. Despite numerous experimental studies, the probabilistic nature of slope failure phenomena remains insufficiently understood. This study employs experimental and statistical analysis using the sandpile model to elucidate slope failures and their magnitudes. The sandpile model involves gradually adding sand to a pile and repeatedly observing its collapse. Experiments were conducted using silica sand No. 8 (fine sand) on base plates with diameters ranging from 5 cm to 12 cm. Shape variations were captured using a depth camera. The results indicate significant geometric changes predominantly at the apex of the sandpile, where the initial breach of stability occurs. The metastable slope angle at the apex of the sandpile induces hysteresis behavior in slope failure. The frequency of occurrence and failure mass deviates from a normal distribution, with smaller magnitudes occurring more frequently and a sharp decrease in frequency for larger magnitudes. This pattern mirrors the frequency-magnitude relationship observed in earthquakes, with the study’s results aligning with the Gutenberg-Richter law, confirming the hypothesis. The b-value obtained from this study falls within the range of frequency-size landslide statistics available in the literature.